2004
DOI: 10.1111/j.1468-3083.2004.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid discoid lupus erythematosus and contact dermatitis: a case report

Abstract: We report a patient with discoid lupus erythematosus (DLE) and associated allergic contact dermatitis (ACD) in the eyelids. In women, ACD caused by nail varnish is frequent and often seen in the eyelids. ACD caused by drugs (e.g. neomycin) is also frequent in this region. However, DLE with periorbital presentation without evidence of systemic or other cutaneous involvement is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Auto-immune diseases, type I diabetes and contact dermatitis follow a Th1 profile and it is not known if this impacts skin reactivity or disease risk. Patients with autoimmune diseases can develop contact dermatitis (Dermendzhiev et al 2018;Niedziela and Bluvshteyn-Walker 2012;Trindade et al 2004;Kosboth et al 2007).…”
Section: Immunosuppression Secondary To Diseasementioning
confidence: 99%
“…Auto-immune diseases, type I diabetes and contact dermatitis follow a Th1 profile and it is not known if this impacts skin reactivity or disease risk. Patients with autoimmune diseases can develop contact dermatitis (Dermendzhiev et al 2018;Niedziela and Bluvshteyn-Walker 2012;Trindade et al 2004;Kosboth et al 2007).…”
Section: Immunosuppression Secondary To Diseasementioning
confidence: 99%
“…This population of patients is especially susceptible to inflammation, so preemptive avoidance of sunscreens with certain ingredients might prevent contact dermatitis. Several case reports have demonstrated that lupus can be exacerbated by contact dermatitis (Barnett, 1990, Shimaoka et al, 2008, Trindade et al, 2004, Van Aerde et al, 2016). Additionally, a study by Güner et al (2013) in which patch testing was applied to both patients with lupus and controls found a statistically significantly higher percentage of positive reactions in the lupus group.…”
Section: Introductionmentioning
confidence: 99%